Modifikasi pati ketela pohon secara kimia dengan oleoresin dari minyak jahe - Diah Susetyo Retnowati; Andre Cahyo Kumoro; Sri Budiyati (Jurnal Rekayasa Proses, 2010)
Recently, starch modifications have been developed and are applied for food, paper and textile industries. In general, chemical modification has been done to improve starch functionality, especially for bread, cake and snack making. In the present work, suspension method was used to modify cassava starch by gingerol of crude ginger rhizome extract at room temperature. The effect of starch/water/gingerol (w/v/v) ratio on swelling power, water solubility, and cross-link density of the modified starch was investigated. In addition, scanning electron microscopy (SEM) analysis were also conducted to observe possible structural changes of the resulting starch. The experimental results showed that reactant composition that had a starch/water/gingerol (w/v/v) ratio of 300:400:0.4 produced modified starch suitable for edible coating with swelling power of 7.3 times, solubility of 6.662 mg/mL and cross-link density of 780.69 chains/cm3. Meanwhile, reactant having starch/water/gingerol (w/v/v) ratio of 300:300:0.3 produced modified starch that could be used for food with swelling power, solubility and cross-linking density of 8.96, 10.55 mg/mL and 203.85 chains/cm2, respectively. The cross-link densities achieved in this modification process were high and reproducible that indicated a strong interaction between starch and gingerol molecules in water as dispersant. However, there were no noticeable changes found from the micrograph of the SEM analysis on the external surface of the cassava starch.